THE USE OF THE GOOGLE CLASSROOM APPLICATION TO IMPROVE BIOLOGY LEARNING OUTCOMES - Aseany, Luh Kadek Agung (Indonesian Journal of Educational Development (IJED), 2023)
The classroom action research conducted at SMA Negeri 1 Kuta Class XI IPA 1 Semester II aimed to improve learning outcomes in Biology subject using the Google Classroom application. The data from this research were collected by administering Biology learning outcomes tests. In analysing the data obtained, descriptive analysis methods were used. The data generated from this research consisted of initial data, cycle I data, and cycle II data. From the initial data, it was found that the class average only reached a score of 76.72 and the learning completeness only reached 69.44%. This data was far below expectations considering that the standard score of Biology at this school was 70. In cycle I, there was an increase and the percentage of learning completeness reached 83.33%. In cycle II, the average class achievement reached 93.3 and the percentage of learning completion reached 100%. The data in cycle II was in line with expectations due to the use of the constructivist Google Classroom application. The conclusion obtained was that the use of the google classroom application could improve Biology learning outcomes for Class XI IPA 1 semester II academic year 2020/2021 at SMA Negeri 1 Kuta.